2008
DOI: 10.1001/archoto.2007.19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Isotonic Nasal Wash (Seawater) in the Treatment and Prevention of Rhinitis in Children

Abstract: Children in the saline group showed faster resolution of some nasal symptoms during acute illness and less frequent reappearance of rhinitis subsequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 17 publications
2
105
0
17
Order By: Relevance
“…30 In a recent study of children with URTIs, daily nasal wash with a sea water-based preparation significantly reduced symptoms in comparison to standard medications. 31 Regrettably, the study agent was not compared to physiological saline.…”
Section: Other Practical Interventionsmentioning
confidence: 99%
“…30 In a recent study of children with URTIs, daily nasal wash with a sea water-based preparation significantly reduced symptoms in comparison to standard medications. 31 Regrettably, the study agent was not compared to physiological saline.…”
Section: Other Practical Interventionsmentioning
confidence: 99%
“…Only the largest study of 401 children found reductions in the number of symptoms, including nasal secretions, obstruction and sore throat in those treated with saline spray 24. The nasal symptom score improved by a MD of 0.31 (95% CI 0.14 to 0.48) on a four-point scale.…”
Section: Indications and Evidencementioning
confidence: 99%
“…Saline solution has no side effects, it can be used as a spray, it is colorless and odorless, cell-friendly, non-chemical, and considered as one of the most effective and safest treatments to clean infected biological surfaces [16,17]. As the TP's physical properties were close to those of the saline solution (with the exception of higher osmotic properties), the investigators proposed saline as CP.…”
Section: Rationale For Selecting Saline Solution As Cpmentioning
confidence: 99%